Application Of Chitosan As A Natural Coagulant In Groundwater Treatment - Junit, Syarifah Nurhanani Syed (Universiti Sains Malaysia, 2017)
One major concern of water supply in Malaysia is the ability to provide safe access drinking water over lifetime consumption to the consumer. Safe drinking water means that it is free from potential risks to human health from exposure to contaminants in drinking water. There are various problems contributing to water pollution for instance the rapid industrialization and increasing population growth. This study was conducted to identify the quality of groundwater extracted from USM groundwater tube well as an alternative for drinking water supply. Jar testing was used to simulate the drinking water supply. Jar testing was used to simulate the performance (removal of colour, turbidity and suspended solids) of natural coagulant (Chitosan) compared to commercial polyaluminium chloride (PACl). The jar testing was conducted at different set of pH (pH 3.0 to pH 10.0) and various coagulant dose (30mg/L, 60mg/L, 90 mg/L, 120mg/L and 150mg/L). The results show that the optimum pH for chitosan and PACl are pH 10.0 with high percentage turbidity removal of 89.93% and percentage suspended solids removal of 85.63%, respectively. Comparison between chitosan and PACl for jar test under varied dosage shows optimum dose of 30mg/L and 150mg/L, respectively. Colour removal was also conducted, but with less significant percentage removal. This shows that chitosan can achieve the same percentage removal as PACl under the same optimum pH but with by far lower dosage. However, all the results shows that the value still exceed the permissible value for drinking water standards by National Water Quality Standards for Malaysia (NWQSM) and the World Health Organization (WHO). Hence, this water should be used for other water classes which require high water demand such as irrigation or recreational purposes.